A Water‐Gated Organic Thin‐Film Transistor for Glyphosate Detection: A Comparative Study with Fluorescence Sensing. Issue 64 (14th October 2020) - Sasaki, Yui; Asano, Koichiro; Minamiki, Tsukuru; Zhang, Zhoujie; Takizawa, Shin‐ya; Kubota, Riku; Minami, Tsuyoshi
Abstract: Invited for the cover of this issue is the group of Tsuyoshi Minami at the University Tokyo. The image illustrates that despite being fabricated with the same polythiophene material, a water‐gated organic thin‐film transistor is a more sensitive device than a fluorescence sensor chip. Read the full text of the article at 10.1002/chem.202003529 . Abstract : " In this study, we employed the competitive coordination of a Cu 2+ ion as a manipulator to achieve highly sensitive detection of the herbicide glyphosate. As shown in the scale of target glyphosate in the cover art, the sensitivity of the WG‐OTFT sensor was higher than that of the fluorescent polymer‐based sensor chip ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 14525 ff. (DOI: 10.1002/chem.202003529 ).